Types of Inanimate Worship in the Glorious Quran - An Analytical Study - Saad Farman Mahmoud (Islamic Sciences Journal, 2025)
ABSTRACT This research deals with the verses of worship of inanimate objects in the Glorious Quran using the analytical study method. The research includes an introduction, four chapters, and a conclusion. The introduction included: the importance of the topic, the reason for choosing the topic, the methodology of the study, and the division of the study. As for the chapters, the first chapter included: the Oneness of Almighty Allah and His transcendence from taking a son. The second chapter included: the prostration of inanimate objects to Almighty Allah . The third chapter included the glorification of inanimate objects to Almighty Allah . As for the fourth chapter, it included the humility and fear of inanimate objects before Almighty Allah . Then the research was concluded with the most important results that were reached. The research showed that the verses of worship of inanimate objects include the consolidation of belief in the souls of the servants, as they depict for us a unique scene of the entire universe as it unifies the Creator, prostrates to Him, glorifies Him, being humble before Him, and fears Him, the Most High, in an expression that is pulsing with every atom in this great universe.